HUBUNGAN PENGETAHUAN DENGAN KEPATUHAN MENJALANI PENGOBATAN PADA PASIEN KANKER PAYUDARA DI RSUD HAJI PROVINSI JAWA TIMUR - Anifah, Fulatul (Sinar : Jurnal Kebidanan, 2024)
Background: Breast cancer is a big problem for both women and is identified with a nature of malignancy that can result in death. Knowledge plays an important role in increasing patient confidence in adherence to treatment. Objective: This study aims to identify the relationship between knowledge and adherence to treatment in breast cancer patients at Haji General Hospital, East Java Province. Method: This type of research uses a quantitative research design with a cross sectional approach. The population of this study were all breast cancer patients at Haji General Hospital, East Java Province and the sample of this study was 104 patients, taken by accidental sampling, data were taken using a questionnaire to measure knowledge and the MMAS-8 questionnaire to measure the level of knowledge and adherence to treatment in breast cancer patients. Results: The results of this study indicate that the knowledge of respondents who underwent breast cancer treatment was mostly in the good and compliant category, namely 36 people (61.0%), a small proportion of sufficient knowledge and compliant as many as 16 people (27.0%), almost all of them had good knowledge and 37 people (82.0%) did not comply, 5 respondents (11.0%) lacked knowledge and did not comply. The results of the statistical test analysis with Chi Square showed that the significant value was p value = 0.024 < (0.05). Based on the results of the analysis, it was found that there was a relationship between knowledge and adherence to undergoing treatment in breast cancer patients at Haji General Hospital, East Java Province.